2020
DOI: 10.1007/s00455-019-10088-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sensory Stimulation on Pharyngo-esophageal Swallowing Biomechanics in Adults with Dysphagia: A High-Resolution Manometry Study

Abstract: Evidence supporting sensory stimulation of swallowing is based mostly on videofluoroscopy and provides little insight into changes to swallowing physiology. In this study, the impact of sensory stimulation on pharyngo-esophageal swallowing biomechanics was investigated in adults with dysphagia using pharyngeal high resolution manometry. Method(s): Fifteen adults (8 males; 45-86 years) with mixed etiology dysphagia were consecutively recruited over a three-month period. PHRM equipment with a 4.2mm pressure cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…The nadir UES pressure, i.e., the lowest UES pressure during relaxation, was also measured. Velopharyngeal, mesopharyngeal, hypopharyngeal, and whole pharyngeal contractile integrals and the UES integrated relaxation pressure were analyzed using a semiautomated analysis portal (Swallow Gateway™) [25][26][27]. These pharyngoesophageal integral metrics are in line with the International High-Resolution Pharyngeal Manometry Working Group recommendations [11]; the metrics used in this study are defined in Table 1.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The nadir UES pressure, i.e., the lowest UES pressure during relaxation, was also measured. Velopharyngeal, mesopharyngeal, hypopharyngeal, and whole pharyngeal contractile integrals and the UES integrated relaxation pressure were analyzed using a semiautomated analysis portal (Swallow Gateway™) [25][26][27]. These pharyngoesophageal integral metrics are in line with the International High-Resolution Pharyngeal Manometry Working Group recommendations [11]; the metrics used in this study are defined in Table 1.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…This portal has excellent interand intra-rater reliability [28,29]. Once the data were uploaded onto the web-based application (www.http//swall owgat eway.com), labeled swallows were identified and six landmarks (including the position of the velopharynx upper margin, hypopharynx upper margin, UES apogee, and UES distal margin, as well as the onset and offset of UES relaxation) were created, which led to the generation of outcomes [26,30]. Specific numbers were assigned for all swallowing events; therefore, the researchers who analyzed the data were blinded with regard to the swallow type (normal, weak THS, and strong THS).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…As many influencing factors have already been investigated, the mechanism of the UES when exposed to acid during food intake is still uncertain. Some authors have observed an increase in sphincter pressure due to acid exposure of the esophagus [ 9 14 ], whereas others did not find any changes in UES pressure when exposed experimentally or spontaneously [ 5 , 15 , 16 ]. Most of these studies have investigated spontaneous reflux events or experimental infusion with hydrochloric acid (HCl) into the esophagus in order to mimic reflux events.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Most of these studies have investigated spontaneous reflux events or experimental infusion with hydrochloric acid (HCl) into the esophagus in order to mimic reflux events. One study has investigated sensory stimulation in terms of swallowed boli, but did not report of significant pressure changes in the UES in relation with a slightly sour bolus [ 14 ]. Following reports on missing UES reactions in patients with reflux [ 17 ], it has even been proposed that the UES may not take part in preventing esophagopharyngeal reflux at all [ 18 ].…”
Section: Background and Aimsmentioning
confidence: 99%
“…Furthermore, and it also may increase the sensitivity of swallowing reflex areas, promote the introduction of sensory impulses before swallowing and produce swallowing reflex to improve swallowing function 36 . However, many scholars 37,38 have pointed out that the effects of ice stimulation for dysphagia are very limited, and the patients’ adherence is not good, more effective interventions are needed.…”
Section: Discussionmentioning
confidence: 99%